Self-Reported School Difficulties and the Use of the School Nurse Services by Adolescent Students - Suoniemi Siru; Rantanen Anja; Koivisto Anna-Maija; Joronen Katja (Switzerland, 2022)
Adolescents are increasingly finding school difficult and physical, mental and social problems increase the risk of exclusion. School health services help to identify problems and prevent them from escalating and the school nurse should be consulted when children are struggling academically. This study explored associations between school difficulties and the use of school health nurse services by 73,680 comprehensive school students with median age of 15.3. The study was based on nationally representative data from the 2017 Finnish School Health Promotion study and analyzed by gender. Difficulties in schooling were common and ranged from 9.9-32.7%. Girls reported difficulties more frequently than boys. Having self-reported difficulties was associated with greater use of school health nurse services, with girls seeking help more often than boys with similar issues and more boys saying they had no need for services. In addition, more self-reported difficulties with schooling were associated with unmet need for school health nurse services. School difficulties were associated with greater use of the school health nurse service use when the data were controlled for background factors. This study highlights shortcomings in access to school health nurse services by children with self-reported school difficulties and that girls were more likely report problems and seek help.